2020
DOI: 10.2215/cjn.05050419
|View full text |Cite
|
Sign up to set email alerts
|

Screening for CKD To Improve Processes of Care among Nondiabetic Veterans with Hypertension

Abstract: Background and objectivesWe conducted a pilot, pragmatic, cluster-randomized trial to evaluate feasibility and preliminary effectiveness of screening for CKD using a triple-marker approach (creatinine, cystatin C, and albumin/creatinine ratio), followed by education and guidance, to improve care of hypertensive veterans in primary care. We used the electronic health record for identification, enrollment, intervention delivery, and outcome ascertainment.Design, setting, participants, & measurementsWe random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This may be caused by albuminuria undertesting, which leads to be under-recognized by clinician. A previous study in 2022 showed that only 9% of American veterans with hypertension who did not know CKD or diabetes had prior urine albumin/creatinine ratio measure ( 29 ). The proportion of ACEi/ARB treatment in CKD adults with ACR (30-300 mg/g) increased from 57.0% in 2001-2006 to 65.3% in 2007-2012, and remained stable thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…This may be caused by albuminuria undertesting, which leads to be under-recognized by clinician. A previous study in 2022 showed that only 9% of American veterans with hypertension who did not know CKD or diabetes had prior urine albumin/creatinine ratio measure ( 29 ). The proportion of ACEi/ARB treatment in CKD adults with ACR (30-300 mg/g) increased from 57.0% in 2001-2006 to 65.3% in 2007-2012, and remained stable thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies targeting process outcomes such as measurement of albuminuria or prescription of renal angiotensin system inhibitors have been successful, whereas those targeting clinical outcomes such as CKD progression or hospitalizations have largely been negative. [22][23][24] Similarly, interventions such as audit and feedback and academic detailing have been effective, 14,25,26 whereas interventions that are primarily on the basis of decision support within the electronic health record have not. 27,28 With these features in mind, we designed our multifaceted intervention to include audit and feedback, academic detailing, and provided several visual aids to enhance the uptake of the intent-todefer strategy and decrease the proportion of patients who undergo early dialysis initiation.…”
Section: Discussionmentioning
confidence: 99%
“… Forest plot of comparison: pharmacist contribution to comprehensive intervention vs. usual care for continuous and dichotomous data concerning clinical outcomes [ 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 24 , 27 , 28 , 29 , 36 , 37 ]. Differential change from baseline in SBP ( a ) and DBP ( b ); patients with an achieved BP goal ( c ); differential change from baseline in eGFR ( d ); #—adjusted for sex, baseline systolic BP, smoking status, body-mass index, and cluster characteristics (mean pharmacist year since graduation); ##—adjusted for the clinical variable at baseline (eGFR), interaction between study group and clinical variable at baseline, and patient’s age, sex, highest level of education, and eGFR, as well as pharmacist being an associate clinician and receiving remuneration for pharmaceutical opinions; BP goal was defined as <140/90 mmHg, except for: &—140/90 mmHg for non-proteinuric CKD and <130/80 for proteinuric CKD; ^—<140/90 mmHg for non-hypertensive patients, and <130/80 mmHg for hypertensive patients; $—<140/90 mmHg for subjects with neither condition, and <130/80 mmHg for DM/CKD patients *—<130/80 mmHg; months of follow-up were shown in brackets.…”
Section: Figurementioning
confidence: 99%